“I'm Afraid My Thesis Has Many Mistakes”: Thesis Writing Anxiety, Its Contributing Factors, and Alleviating Strategies - Kawengian, Grisel Englin; Subekti, Adaninggar Septi (Journal of English Teaching and Learning Issues, 2024)
The present study intends to investigate the possible contributing factors of thesis writing anxiety and the possible strategies that could be taken to help reduce thesis writing anxiety. For these purposes, this study conducted interviews with six Indonesian learners of English in English language departments and two Indonesian English lecturers who were thesis advisors. From Thematic Analysis, this study found two factors contributing to learners' anxiety. These were perceived inability to express ideas in good English writing and getting negative evaluations from their respective thesis advisor. Furthermore, three strategies were believed by both learners and advisors to help reduce learners' thesis writing anxiety. These included using grammar checker tools to improve writing quality and learning grammar, reading journal articles to improve learners’ mastery of the research topic, and creating a positive atmosphere for consultation sessions. Based on the findings, it is suggested, among others, that exposure to various academic texts and the use of grammar in academic contexts should be increased earlier in the curricula. Thesis advisors are also encouraged to show support and instill optimism. Contributions of this study are stated alongside several suggested directions for future studies.